Embracing the Benefits of an Online Learning Approach: Exploring the New Teaching Set-up in the Academic Sphere - Gumarang Jr., Bernardo K.; Eleponio, Jeyfa C.; Ibasco, Richelle S. (CV. Literasi Indonesia, 2025)
The study explored the benefits of the online learning approach as a new setup of teaching modality. Specifically, it examined the benefits as experienced by the students. Qualitative in-depth interviews were utilized in this study, and purposive sampling was used to select the participants. The participants were students invited from one of the universities in the Philippines. Thematic analysis was employed to extract themes from the transcribed interviews of the participants. The study revealed six themes: Self-Directed Learning, Breaking the Culture of Being a Dependent Learner, Online Learning Broadens Academic Horizons, Online Learning Improves Academic Performance, Online Learning Offers Students the Accessibility of Time, and Opportunity to Pursue a Degree from Home. The findings suggest that this new setup of teaching should be adopted by all universities to cater to the needs of students who are unable to attend school due to certain circumstances and who wish to complete their college degrees.